2011
DOI: 10.1111/j.1442-1984.2011.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and plasticity of endangered shrubLindera melissifolia(Lauraceae) seedlings under contrasting light regimes

Abstract: Lindera melissifolia (Walt.) Blume seedlings were raised in a growth chamber to determine the effects of light availability on shoot growth pattern, and basic leaf and stem growth. Lindera melissifolia seedlings exhibited a sympodial shoot growth pattern for 3 months following emergence from the soil medium, but this pattern was characterized by a reduction in leaf blade area approximately 30 days after emergence, followed by increases in leaf blade area. Seedlings receiving low light were 76% taller than seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 84 publications
3
5
0
Order By: Relevance
“…These results are consistent with other studies that have shown that L. melissifolia is highly plastic in response to shading (Wright 1990b, Aleric and Kirkman 2005, Lockhart et al 2012, Lockhart et al 2013. Consistent with Lockhart et al (2012), we found that L. melissifolia seedlings grown under higher light conditions allocate greater resources to roots. While L. melissifolia seedlings expressed clear morphological patterns in response to varied light and moisture, the role of interaction between these two factors remains unclear.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…These results are consistent with other studies that have shown that L. melissifolia is highly plastic in response to shading (Wright 1990b, Aleric and Kirkman 2005, Lockhart et al 2012, Lockhart et al 2013. Consistent with Lockhart et al (2012), we found that L. melissifolia seedlings grown under higher light conditions allocate greater resources to roots. While L. melissifolia seedlings expressed clear morphological patterns in response to varied light and moisture, the role of interaction between these two factors remains unclear.…”
Section: Discussionsupporting
confidence: 95%
“…In our field observations, L. melissifolia adults occurred under a variety of overstory conditions at both sites ranging from 5.5-86.6% transmittance as measured with a quantum line sensor, and co-occurred with both full sun-and shade-tolerant species. Leaves of adults present in the areas of highest transmittance had a curled form, similar to those described by Aleric and Kirkman (2005) and Lockhart et al (2012) under high light and presumed stress. Other studies have observed that L. melissifolia has decreased photosynthetic efficiency under conditions of higher light (Aleric and Kirkman 2005, Wright 1990b) and concluded this could lead to decreased competitive ability in open canopy areas with low moisture (Wright 1990b).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations